Screening and mutation analysis of phenylalanine hydroxylase deficiency in newborns from Jiangxi province - Zeng, Baitao; Lu, Qing; Chen, Shaohong; Guan, Huizhen; Xu, Xiaolan; Zou, Yongyi; Wang, Feng; Huang, Shuhui; Liu, Yanqiu; Yang, Bicheng (Frontiers in Genetics, 2023)
Phenylalanine hydroxylase deficiency (PAHD) is autosomal recessive disorder of amino acid metabolism and caused by mutations in the phenylalanine hydroxylase (PAH) gene. PAHD incidence differed significantly in each Chinese province. Without timely and appropriate intervention, the amino acid metabolism may impair cognitive development and neurophysiological function. Thus, by Neonatal PAHD screening to early detection and treatment, the prognosis can be excellent. In this study, 171 PAHD patients between October 1997 and December 2021 were diagnosed in about 5,541,627 newborns from Jiangxi province. The screening rate rose from 1.65% to 97.68%. We speculated PAHD incidence of Jiangxi province was about 1/32407. Taking advantage of Sanger sequencing and the multiplex ligation-dependent probe amplification (MLPA) analysis, we summarized the PAH mutation spectrum in Jiangxi province for the first time. Missense variants accounted for 57.3% of the total and c.728G>A had the highest frequencies (14.1%). This mutation spectrum is very meaningful to improve the diagnostic rate of PAHD and to increase the accuracy genetic counseling. We compared the observed phenotype of the predicted phenotype based on the genotype. The overall consistency rate was 77.4%. This study offers data for the genotype-phenotype prediction suitable for Chinese population.